Polymerase chain reaction-free detection of hepatitis B virus DNA using a nanostructured impedance biosensor - Chen, Chun-Cheng; Lai, Zi-Lun; Wang, Gou-Jen; Wu, Chun-Ying (Biosensors & bioelectronics, 2016)
A polymerase chain reaction (PCR)-free technique for the effective detection of genomic length hepatitis B virus (HBV) DNA is described in this study. The honeycomb-like barrier layer of an anodic aluminum oxide (AAO) film having a uniform nanohemisphere array was used as the substrate of the sensing electrode. A 30-nm gold film was sputtered onto the AAO barrier layer surface as the electrode, followed by electrochemical deposition of gold nanoparticles (GNPs) on the hemisphere surface. A specially designed single-strand 96-mer gene fragment of the target genomic DNA of HBV based on the genome sequences of HBV was immobilized on the nanostructured electrode as the capture probe. Target HBV DNA obtained from clinical samples was hybridized to the sensing probes. Detection results illustrate two dynamic linear ranges, 102–103 and 103–105.1 copies/mL, having R2 values of 0.801 and 0.996 could be obtained, respectively. The detection limit of the proposed sending scheme was measured to be 111 copies/mL. The total of 45 target samples, including 20 samples with HBV concentration being lower than 102 copies/mL and 25 samples with HBV concentration being in the range of 103–105.1 copies/mL, were used for real test. The concentration of these 45 HBV DNA samples was measured by the COBAS Ampliprep system. Comparing the measured results of the COBAS Ampliprep and our system, it was illustrated that the HBV DNA concentrations measured by the proposed method in this study had a high linear correlation with the COBAS Ampliprep, having R2 values of 0.983. The proposed sensing scheme is highly feasible for future clinical applications. •We report a polymerase chain reaction (PCR)-free technique for effective detection of genomic length hepatitis B virus (HBV) DNA.•A single-strand 96-mer gene fragment of the target genomic DNA of HBV based on the genome sequences of HBV was specially designed.•The detection limit of the proposed sending scheme was measured to be 111 copies/mL.•The HBV DNA concentrations measured of 45 patients by the proposed method had a high linear correlation with the COBAS Ampliprep, having R2 values of 0.983.